Inovasi Pembelajaran Matematika: Pemanfaatan Papan Geoboard dalam Memperkuat Pemahaman Luas Bangun Datar di Kelas IV SD - Rahayu, Fuji; Risnawati; Hamdani, M. Fikri (Journal of Practice Learning and Educational Development, 2026)
Mathematics learning in elementary schools, especially in the subject of flat shapes, still faces various problems, including low student understanding of concepts due to abstract presentation of material and lack of use of concrete learning media. This condition causes students to tend to memorize formulas without deeply understanding the meaning of the concept of area. Therefore, learning innovations are needed that can bridge abstract mathematical concepts to make them more concrete and easier to understand, one of which is through the use of Geoboard media. This study aims to determine the effect of using Geoboard media in strengthening the understanding of the concept of flat shapes in fourth-grade elementary school students. This study used a quantitative method with a quasi-experimental design of the nonequivalent control group type. The research subjects consisted of two classes, namely the experimental class, which received learning using Geoboard media, and the control class, which received conventional learning. The research instrument was a test of understanding of the concept of flat shape area that had undergone validity and reliability tests. The data were analyzed using descriptive statistics and inferential tests in the form of an independent sample t-test. The results showed that the average score for understanding of the concept among students in the experimental class was higher than that of the control class, and there was a significant difference between the two groups. These findings indicate that the use of Geoboard is effective in improving understanding of the concept of flat shape area. Thus, Geoboard is recommended as an alternative mathematics learning medium in elementary schools to support meaningful and student-centered learning.